Development of Novel Semi-Stranded Windings for High Speed Electrical Machines Enabled by Additive Manufacturing - Ahmed Selema; Mohamed N. Ibrahim; Peter Sergeant (Applied Sciences, 2023)
Recent advances in electrical machines and energy storage technologies make electric vehicles (EVs) feasible replacements to conventional internal combustion engines. One of the main challenges of high speed electrical machines is providing maximum output power with minimum energy losses, weight, and volume. At high frequency operation, the conductors of AC electrical machines can suffer from skin and proximity effects. This results in high AC losses in the machine windings and can eventually lead to machine failure. In this paper, a novel design for a semi-stranded coil is proposed to limit these undesirable effects. Enabled by additive manufacturing (AM) technology, this sophisticated design is 3D printed using ultralight aluminum alloy. Finally, the AC performance of this coil is measured and compared with conventional single-strand copper coil at different frequency levels. It is found that the proposed design can effectively limit the eddy current losses in the high frequency domain.